(3JGQjN GdTGes
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG HOGjI hHYO , agPg ChGQb CPcQ ajgG eG JjSQ GdEWdGY Ydjg hSgd GdhUhd Edjg ef cJH JhGQjN GdESdGe ajeG jJYdb HaGVFd OeTb , hZjQgG ef CQV GdTCe haVGFd LGeYgG GdeYXe s
(3BNQgG (B:s
(3Ke jgdc Gddg jCLhL heCLhL , hJNQL GdCQV HQcGJgG , hHYOg JgH QjM ef Gdjef aJbHV CQhGM GdeDefjf , hJbhe GdSGYI Ydi TQGQ GdNdb hGab GdaQGZ ef cJGHJg s
(3HgG fXGe GdJYbjHIs
(3jJVef JGQjN GdTGe haVGFd OeTb hLGeYgG hQJHg Ydi SJI CHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs